Factors that are affecting individual job performance case study in SAJ Holdings Sdn Bhd, Muar / Fairuz Abu Bakar - Abu Bakar, Fairuz (Faculty of Business and Management, 2010)
Job performance is the important thing that each organization should take consideration seriously. This is because performance will give much impact to the outcome and directly toward the organization performances. Thus, this study aims to see the individual’s job performance among non-executive employees in SAJ Holdings Sdn Bhd, Muar because most of these groups always contact directly to their customers. So, good performance of employees will satisfy the customer and also giving a good image or the organization to the public.